El capital de trabajo como herramienta fundamental para el desarrollo de las MYPES - Huapaya Ríos, Juan Pablo (2018)
MSc. Ambar Yudith Selpa Navarro MSc. Daisy Espinosa Chongo of the Department of Accounting and Finance professors at the University of Matanzas Camilo Cienfuegos-Cuba, mentioned in her article on: Working Capital Management as a process of Financial Operations Management, that "in today's world where companies seek to maintain afloat in an eminently capitalist market, it is essential to draw up strategies that advocate the development of large, medium and small associations. In this sense, it is necessary to use techniques that help the correct development of companies in terms of the use of working capital as a source of development. The country is not exempt from this process and for decades seeks the continuous improvement of all branches of the economy, locating the tourism sector as one of the largest sources of income of the island. It is evident then the importance of the fact that a whole system of knowledge about productive activities be developed, studies and investigations be deepened that allow laying the theoretical foundations that sustain the improvement of the elements that make up this essential branch and guarantee the quality of its practice and obtaining better results. It is then in this sense an important fact, that managers and staff in general of these entities dominate management and financial elements that help the proper development of economic processes that are carried out in them, to ensure the quality of service and is reversed at the end of the chain in customer satisfaction. As a result of the foregoing, the special importance that the management of working capital as a management tool contributes to the development of Mypes, to achieve the efficient management of resources and business operations, as well as obtain the expected results in correspondence with the proposed organizational objectives and pursued either with lower risk and better levels of growth and performance. " "The Working Capital Administration determines the liquidity position of the company, and liquidity is necessary for survival." F. Weston and E. Brigham (1994).